Effect of Sm3+ on the Spectroscopic Properties of Poly(N-vinylisobutyramide) - Chen, Zhidu; Yu, Shoufu; Guo, Shaofen (Asian Journal of Chemistry, 2014)
In this paper, the effect of Sm3+ on the spectroscopic properties of poly(N-vinylisobutyramide) (PNVIBA) polymer was investigated by using ultraviolet-visible, FT-IR and fluorescent spectroscopy techniques. It was found that Sm3+ might coordinate with N atoms in the PNVIBA side chain and form the Sm3+-PNVIBA complex. After forming the Sm3+-PNVIBA complex, the fluorescence emission intensity at 315 nm was significantly enhanced 1.73 times comparing with that of the PNVIBA polymer, in which the efficient intramolecular energy transfer from Sm3+ to PNVIBA might be occurred. The Sm3+-PNVIBA complex could transform the short ultraviolet radiation to longer wavelength UV-B band radiation. However, the low critical solution temperature (LCST) of PNVIBA was not obviously changed after the addition of a small amount of Sm3+. This thermosensitive complex might be a potential functional material in many fields.